THE DECISION OF INVESTING IN INFORMATION AND COMMUNICATION TECHNOLOGY IN SMALL AND MEDIUM ENTERPRISES - DÍEZ, Javier García; MOMPÓ, Rafael; CORONADO, Miguel López; GRANADOS, Judith Redoli (Ecoforum Journal, 2016)
A diagnostic tool on the decision of investing in Information and Communication Technology (ICT) in small and medium enterprises (SME) suggested in Judith Redoli et al. (2008), showed its usefulness helping to understand how an enterprise uses ICT and ‘‘how’’ and ‘‘when’’ a company should incorporate new technological elements. The model was applied successfully in the assessment of 500 SME; as a result a technology deployment project was given to each enterprise in which a priority project was also defined. This short paper presents the second part of that study: a second assessment was made to those SME oriented to detect whether the enterprises on which the analysis was conducted did achieve the deployment of the technologies identified within six months, and the relationship between this fact and the existence of an associated grant. On the other hand, in this research the correlation between the priority project established in the first assessment and the one that was finally completed was demonstrated.